Digital Philanthropy: Ethical Dilemmas and the Transition to Digital Society in Jember Regency - Khoirul Anam; Zaenal Abidin (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The accelerating transition toward digital society has profoundly transformed the governance architecture of contemporary philanthropy, particularly within Islamic charitable institutions increasingly dependent on platform-based systems for fundraising, communication, and public accountability. In Indonesia, the digitalization of Zakat, Infak, and Sedekah (ZIS) institutions has expanded fundraising accessibility, strengthened donor participation, and enhanced operational efficiency through the integration of crowdfunding platforms, social media campaigns, QR-code payments, mobile banking, and real-time reporting systems. However, despite the growing institutional adoption of digital philanthropy, existing scholarship continues to emphasize technological optimization and fundraising effectiveness while providing limited critical attention to the ethical contradictions emerging within digitally mediated philanthropic governance. This study critically examines the ethical dilemmas surrounding digital philanthropy practices in ZIS institutions in Jember Regency during the transition toward a digital society. Employing a qualitative multiple-case study design grounded in an interpretivist paradigm, data were collected through semi-structured interviews, non-participant observations, and institutional documentation involving 21 participants consisting of institutional managers, donors, and beneficiaries. The data were analyzed using reflexive thematic analysis supported by NVivo 14 software. The findings reveal that digital philanthropy significantly strengthens bureaucratic efficiency, real-time accountability, participatory donor engagement, and geographical distribution capacity. Nevertheless, the study simultaneously identifies persistent ethical tensions related to donor data confidentiality, platform dependency, transparency of ujrah, informational asymmetry, and the commodification of poverty within emotionally driven digital fundraising campaigns. The study argues that digital philanthropy should not be understood merely as a technological fundraising innovation, but as a contested socio-technical and moral governance system where institutional legitimacy, algorithmic visibility, ethical accountability, and public trust continuously intersect and conflict. The findings contribute theoretically by extending discussions on techno-moral legitimacy and platformized philanthropy within Islamic charitable governance while offering practical insights for developing ethically sustainable and socially responsible digital philanthropic ecosystems.